Melatonin-induced phase and dose responses in a diurnal mammal, Funambulus pennantii - Soni S.K.; Kumar D.; Singaravel M. (My University, 2025)
Melatonin, an essential pineal hormone, acts as a marker of the circadian clock that regulates biological rhythms in animals. The effects of exogenous melatonin on the circadian system of nocturnal rodents have been extensively studied; however, there is a paucity of studies on the phase-resetting characteristics of melatonin in diurnal rodents. We studied the phase shifting effects of exogenous melatonin as a single melatonin injection (1 mg/kg) at various phases of the circadian cycle on the circadian locomotor activity rhythm in the palm squirrel, Funambulus pennantii. A phase response curve (PRC) was constructed. Adult male squirrels (N = 10) were entrained to a 12:12 h light-dark cycle (LD) in a climate-controlled chronocubicle with food and water provided ad libitum. After stable entrainment, squirrels were transferred to constant dark condition (DD) for free-running. Following stable free run, animals were administered a single dose of melatonin (1 mg/kg in 2% ethanol-phosphate buffered saline (PBS) solution) or vehicle (2% ethanol-PBS solution) at circadian times (CTs) 3 h apart to evoke phase shifts. The phase shifts elicited at various CTs were plotted to generate the PRC. A dose response curve was generated using four doses (0.5, 1, 2 and 4 mg/kg) administered at the CT of maximum phase advance. Melatonin evoked maximum phase advances at CT0 (1.23 ± 0.28 h) and maximum phase delays at CT15 (0.31 ± 0.09 h). In the dose response experiment, maximal phase shifts were evoked with 1 mg/kg. In contrast, no significant shifts were observed in control groups. Our study demonstrates that the precise timing and appropriate dose of melatonin administration is essential to maximize the amelioration of circadian rhythm–related disorders in a diurnal model. © 2020 Taylor & Francis Group, LLC.